Efek Budget Ratcheting Pada Anggaran Pemerintah Kabupaten/Kota Provinsi Sumatera Barat - Annisa Ayu Safitri; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2020)
This research is aimed to know the effect of budget ratcheting in local revenue, balancing funds, and capital expenditures. This study also examines how the effects of budget ratcheting in the relationship between local revenue to regional expenditures. This research is categorized as causative research. The population in this study are all regencies / cities in the province of west sumatra, which are 12 districts and 7 cities. Sampling in this study was conducted using total sampling. The data in this study were sourced from the district / city local government financial statements in west sumatra province in 2014-2018. The data in this study were processed using spss 23. The results of this study indicate that there is a budget ratcheting effect in local revenue, balance funds and capital expenditures. the results of this study also show that local revenue influences regional expenditure and budget ratcheting to weaken the relationship between the two.